PENGARUH PENGGUNAAN MODEL COOPERATIVE SCRIPTS TERHADAP KEMAMPUAN MENGANALISIS TEKS EKSPLANASI SISWA KELAS XI SMA N 9 PADANG - Viadona Trisna Dewi; Asri Wahyuni Sari; Indriani Nisja (Jurnal Inovasi Penelitian, 2021)
The problem in this study is that students are less skilled in analyzing and there is no student interest in learning explanatory texts. This study aims to describe the ability to analyze explanatory text without and using the Cooperatve Scripts model and the effect of using the Cooperatve Scripts model on the ability to analyze explanatory text in class XI SMA N 9 Padang. This type of research is quantitative using experimental methods. The design of this research is The Randomized Posttest Only Control Group. The population of this study were all students of class XI SMA N 9 Padang. The results of this study can be considered as follows. First, the level of explanatory text analysis without using the Cooperatve Scripts model, students of class XI SMA N 9 Padang obtained an average score of 74.96 with a classification of 66-75% which is more than adequate (LdC). Second, the level of ability to analyze explanatory text with the Cooperatve Scripts model, students of class XI SMA N 9 Padang obtained an average score of 83.40 with a classification of 76-85% including good (B). Third, from the results of data analysis, the alternative hypothesis (H1) is accepted at a significant level of 95% and dk = n-2 because tcount> ttable (5.27> 1.67). In other words, there is an effect of the Cooperatve Script model on the Ability to Analyze Explanatory Texts in class XI students of SMA N 9 Padang.